Методичні основи пропаганди охорони праці на підприємствах АПК - Рогач, Юрій Петрович; Рогач, Юрий Петрович; Rohach, Yurii (ТДАТУ, 2014)
UK: B статті наведено методичні основи пропаганди охорони праці на підприємствах АПК. EN: In article it is induced methodical bases of propagation of a labor safety at the agriculture enterprises.
Methodical bases of propagation of the labour Safety at the agriculture enterprises
Keywords: методика; пропаганда; прийоми